2006
DOI: 10.1016/j.clpt.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics of erlotinib in patients with solid tumors and exposure-safety relationship in patients with non–small cell lung cancer

Abstract: The long half-life of erlotinib supports the current once-daily dosing regimen at 150 mg/d. Effects of covariates on erlotinib clearance and correlations with adverse event severity were provided to aid in the detection of a treatment-emergent effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 24 publications
12
155
0
Order By: Relevance
“…However, there was significant overlap in the range of PK values with patients who had no rash. No correlation was found with diarrhea 31. Two clinical exposure–response studies have been reported.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 98%
See 1 more Smart Citation
“…However, there was significant overlap in the range of PK values with patients who had no rash. No correlation was found with diarrhea 31. Two clinical exposure–response studies have been reported.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 98%
“…Erlotinib exposure has been significantly correlated with rash in several studies 31. However, there was significant overlap in the range of PK values with patients who had no rash.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 99%
“…This deficit can partly be attributed to the traditional nature of cancer drugs, being highly toxic and the use of maximum tolerated doses, making the use of a therapeutic PD endpoint of limited value. Although this latter point may be disputed, it is clear that the majority of PD modeling efforts for anticancer drugs have been models for drug-induced myelosuppression, a common dose-limiting toxicity (42)(43)(44)(45). With the advent of imatinib at the turn of the century, the gateway for targeted anticancer therapy was opened that escalated the opportunities and altered the landscape for multidrug combination cancer chemotherapy as less toxic targeted drugs could be considered (46).…”
Section: Hybrid Physiologically Based Pharmacokinetic/pharmacodynamicmentioning
confidence: 99%
“…Upon absorption, erlotinib is heavily protein-bound (93-95 %) to albumin and α-1 acid glycoprotein, and its median half-life is 36 hours [37]. There is no significant association with drug clearance and gender, weight, or age [33].…”
Section: Pharmacologymentioning
confidence: 93%